Metachronous Bilateral Granulocytic Sarcoma of the Testis in a Young Adult: A Report of an Unusual Entity. (5th May 2014) - Hızlı, Fatih; Aksüt, Hakan; Mengeloğlu, Aslı; Sarı, İbrahim; Güven, Eşref Oğuz; Başar, Halil
Abstract : Granulocytic sarcomas are rare tumors composed of neoplastic blood cells, typically occurring during the course of acute nonlymphoblastic leukemia or before its onset. We present a case of a 23-year-old young adult man with metachronous granulocytic sarcoma of the testis without hematologic manifestations who was diagnosed with granulocytic sarcoma (GS). The patient was treated with right orchiectomy but relapsed with a left testicular mass 16 months later when a left orchiectomy was performed. The patient has been free of disease for 13 months following the left orchiectomy. This case highlights a rare hematologic cancer that urologists and pathologists should be aware of since it can present as a testicular mass. Only 3 cases of testicular GS without an associated hematologic disorder have been described. To the best of our knowledge, our patient is the first reported case in the English literature of metachronous GS of the testis with no evidence of hematologic disorder.